Discovery Learning : Implementation In Social Learning Assisted Interactive Digital Teaching Materials To Improve Student Learning Outcomes - Wiwik Maladerita; Azwar Ananda; Maria Montesori (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The use of teaching materials in social studies is very important because it can increase effectiveness in improving student learning outcomes. This study aims to determine the effect of the use of interactive digital teaching materials in social studies learning with discovery learning model on student learning outcomes SMPN Nilau Tapan South Coastal District, West Sumatra. This quasi-experimental study used a posttest-only group design. Sampling using purposive sampling technique. The results of this study indicate that there is a significant effect of the application of interactive digital teaching materials with discovery learning model on student learning outcomes. Thus, the use of interactive digital teaching materials with discovery learning models can be used by teachers to accommodate students ' cognitive abilities so that student learning outcomes can increase.